Simultaneous determination of 20 trace organic chemicals in waters by solid-phase extraction (SPE) with triple-quadrupole mass spectrometer (QqQ-MS) and hybrid quadrupole Orbitrap high resolution MS (Q-Orbitrap-HRMS). (November 2016) - Chen, Wei; Huang, Huanfang; Chen, Chang-Er; Qi, Shihua; Price, Oliver R.; Zhang, Hao; Jones, Kevin C.; Sweetman, Andrew J.
Abstract: A sensitive method for simultaneous determination of 20 trace organic chemicals (TOrCs, including preservatives, antioxidants, disinfectants, oestrogens, alkyl-phenols and bisphenol-A) in surface water and wastewater has been developed and validated based on the optimisation of solid-phase extraction (SPE) followed by liquid chromatography-mass spectrometry (LC-MS) analysis. 500 mL acidified (pH = 2.5) water samples were pre-concentrated by Supel-Select HLB cartridge (200 mg, 6 mL) and eluted with 12 mL mixture of acetonitrile and ethyl acetate (50:50, v/v). This optimised SPE procedure could provide >75% recoveries for the majority of TOrCs. The instrumental methods were developed using two different LC-MS systems: a triple-quadrupole MS (QqQ-MS) and a hybrid quadrupole Orbitrap high resolution MS (Q-Orbitrap-HRMS). Both showed good performance data, but the former system provided better linearity and method precision, with the latter system providing 2–33 times lower detection limits. Different matrix effects were observed for both systems: No remarkable matrix effects were observed for Q-Orbitrap-HRMS but significant matrix effects were found in influent and river water samples for the QqQ-MS. This analytical method was subsequently employed to analyse the TOrCs in river waters and wastewaters from China successfully, which confirmed its applicability to environmental samples. Graphical abstract: Highlights: Twenty trace organic chemicals in waters were simultaneously determined by two different LC-MS systems. Triple-quadrupole MS (QqQ-MS) and hybrid quadrupole Orbitrap high resolution MS (Q-Orbitrap-HRMS) instruments were compared. Fewer matrix effects and lower detection limits were provided by Q-Orbitrap-HRMS, with more stable performance for the QqQ-MS.